Restorative care ambulation / [PRIMEDIA Healthcare] - Primedia Healthcare (Carrollton, Tx. : Trinity Healthforce Learning, 2004)
(Producer) Discusses a restorative ambulation program and the components necessary to restore ambulation functionality to residents
VHS
Keywords: Gait; Aged; Rehabilitation; Self-help devices